Factors Related to Incidence of Hypertension in Eldery at Narang Public Health Center - Hantip, Paskalis Charvalo Putra; Tira, Deviarbi Sakke; Tedjuhinga, Indriati A. (Timorese Journal of Public Health, 2022)
Hypertension is a very serious degenerative disease in the current era. Hypertension is included in the category of the silent disease or the silent killer, this is because someone who suffers from hypertension does not realize that he has hypertension or has not even had his blood pressure checked before. Narang Health Center is one of the health centers with high hypertension cases in West Satar Mese District, Manggarai Regency. Data on hypertension cases at the Narang Health Center in 2018 were 431 cases, in 2019 there were cases that decreased to 175 while in 2020 there was a high increase of 484 problems. The purpose of this study was to determine the relationship between salt consumption, family history, alcohol consumption, knowledge, physical activity, and the incidence of hypertension in the elderly. This type of research is an analytical survey. The design of this research is cross sectional. The population is elderly people aged 60-69 years. The sampling technique was a random sampling system with 142 respondents. Data were collected using interview methods and questionnaires. Statistical test using chi square technique. The results of the study showed a relationship between salt consumption (p value = 0.000), family history (p value = 0.000), knowledge (p value = 0.000) physical activity (p value = 0.000), obesity (p value = 0.001), and the incidence of Hypertension in the elderly is located in the work area of ​​the Narang Community Health Center, West Satar Mese District, Manggarai Regency and there is no relationship between alcohol consumption and the incidence of hypertension in the elderly (p value = 1,000) located in the Narang Health Center Work Area, West Satar Mese District, Manggarai Regency. It is recommended that the extension workers at the Health Center to be more active in conducting counseling about hypertension